Analisis Kualitas Informasi Akuntansi Pada BAZNAS Kota Jambi - Sulis Handayani; Rofiqoh Ferawati; Mohammad Orinaldi (Lembaga Pengembangan Kinerja Dosen, 2023)
ABSTRACT This study aims to find out about the quality of accounting information at BAZNAS Jambi City and what are the obstacles in implementing the quality of accounting information at BAZNAS Jambi City in managing BAZNAS financial reports in terms of PSAK 109. The type of this research is qualitative research, namely the field research method. documentation and interviews. In collecting the data, the researcher involved several staff of BAZNAS Jambi City. Based on the results of the study indicate that the general obstacle in the application of SIA at BAZNAS Jambi city is constrained in Human Resources because the number of employees is very limited, besides that the problem of educational background that is not in accordance with the field of work taken will affect the quality of accounting information in the presentation of the report. Finance.